ACCF/ACG/AHA 2008 Expert Consensus Document on Reducing the Gastrointestinal Risks of Antiplatelet Therapy and NSAID Use : A Report of the American College of Cardiology Foundation Task Force on Clinical Expert Consensus Documents - Bhatt, Deepak L; Scheiman, James; Abraham, Neena S; Antman, Elliott M; Chan, Francis K L; Furberg, Curt D; Johnson, David A; Mahaffey, Kenneth W; Quigley, Eamonn M; Harrington, Robert A; Bates, Eric R; Bridges, Charles R; et al. (Journal of the American College of Cardiology, 2008)
Often the topic is the subject of ongoing investigation. [...]the reader should view ECDs as the best attempt of the ACCF and other cosponsors to inform and guide clinical practice in areas where rigorous evidence may not be available or the evidence to date is not widely accepted. The COX-1 pathway is the predominant constitutive pathway; prostaglandins derived from this enzyme mediate many effects, most notably facilitating gastroduodenal cytoprotection, renal perfusion, and platelet activity.\n Peer Reviewer Representation Consulting Fees/Honoraria Speakers' Bureau Ownership/Partnership/Principal Research Institutional or Other Financial Benefit Expert Witness or Consultant Dr. Eric R. Bates Official Reviewer--ACCF Task Force on Expert Consensus Documents * Sanofi-Aventis None None None None None Dr. Craig B. Clark Official Reviewer--ACCF Board of Governors None None None None None None Dr. Robert A. Harrington Official Reviewer--ACCF Board of Trustees Bayer* Bristol-Myers Squibb Sanofi-Aventis None None AstraZeneca* Bayer* Bristol-Myers Squibb* Sanofi-Aventis* None None Dr. John Inadomi Official Reviewer--ACG AstraZeneca TAP Pharmaceuticals None None None None None Dr. Philip Katz Official Reviewer--ACG AstraZeneca* Horizon Therapeutics TAP Pharmaceuticals AstraZeneca* Santarus TAP Pharmaceuticals None None None None Dr. Laurence Sperling Official Reviewer--AHA None None None None None None Dr. Daniel I. Simon Official Reviewer--AHA * Sanofi-Aventis None None None None None Dr. Jeffrey S. Berger Content Reviewer--ACCF Prevention Committee None None None None None None Dr. Roger S. Blumenthal Content Reviewer--ACCF Prevention Committee None None None None None None Dr. Jeffrey J. Cavendish Content Reviewer--ACCF Prevention Committee None * Bristol-Myers Squibb/Sanofi-Aventis* None None None None Dr. Jose G. Diez Content Reviewer--ACCF Cardiac Catheterization and Intervention Committee * Sanofi-Aventis None * Sanofi-Aventis None None None Dr. Steven P. Dunn Content Reviewer--ACCF Prevention Committee None None None None None None Dr. Pamela B. Morris Content Reviewer--ACCF Prevention Committee AstraZeneca Pfizer Takeda Pharmaceuticals North America None None None None None Dr. Srihari S. Naidu Content Reviewer--ACCF Cardiac Catheterization and Intervention Committee None None None None None None Dr. Robert S. Rosenson Content Reviewer--ACCF Task Force on Clinical Expert Consensus Documents None * AstraZeneca* None * AstraZeneca* None None Dr. Nanette K. Wenger Content Reviewer--ACC/AHA Guidelines on the Management of Patients With Unstable Angina/NSTEMI AstraZeneca Pfizer Schering-Plough* None None Pfizer* Sanofi-Aventis* None None Ms. Marie J. Williams Content Reviewer--ACCF Cardiac Catheterization and Intervention Committee None None None None None None * This table represents the relationships of peer reviewers with industry and other entities that were reported as relevant to this topic during the document development process.